2021
DOI: 10.3233/thc-181373
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the effect of an arch support functional insole on walking and jogging in young, healthy females

Abstract: BACKGROUND AND OBJECTIVE: The aim of this study was to explore the effectiveness of arch support functional insoles to prevent metatarsalgia. METHOD: Twenty-five healthy females participated in the study. A Vicon motion capture system was used to collect kinematics data of the lower limb. An AMTI force plate was used to record the vertical ground reaction force (GRF), and the Novel Pedar-X System was used to measure foot pressure while subjects wore normal insoles or functional insoles with an arch support dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…As illustrated above, a faster COP velocity during the FFCP and FFPOP may benefit runners, but how fast is optimal has yet to be determined. A higher arch support also slightly decreased the third COPV total peak, which may be because that a higher arch support would increase the contact with the midfoot region during running ( Zhao et al, 2021 ), slowing down the COP velocity before heel-off. Previous studies have shown that the COP velocity during walking served as an indicator for foot mobility and function during the early healing phase after calcaneal fractures ( Klopfer-Kramer et al, 2022 ).…”
Section: Discussionmentioning
confidence: 98%
“…As illustrated above, a faster COP velocity during the FFCP and FFPOP may benefit runners, but how fast is optimal has yet to be determined. A higher arch support also slightly decreased the third COPV total peak, which may be because that a higher arch support would increase the contact with the midfoot region during running ( Zhao et al, 2021 ), slowing down the COP velocity before heel-off. Previous studies have shown that the COP velocity during walking served as an indicator for foot mobility and function during the early healing phase after calcaneal fractures ( Klopfer-Kramer et al, 2022 ).…”
Section: Discussionmentioning
confidence: 98%
“…This is not in line with previous walking study, which indicated smaller peak GRF in arch-support insoles in women. 14 Such discrepancies could be due to gender effect because gender differences would have different anthropometry and movement patterns. 34 Neuromuscular control between men and women is likely to be an important factor influencing lower extremity mechanics during the stop-jump task.…”
Section: Discussionmentioning
confidence: 99%
“…The application of orthotic insoles might be useful to compensate elevated body weight (Hotfiel et al, 2017). Zhao et al (2018a) and Zhao et al (2018b) suggested that arch support functional insoles could effectively improve…”
Section: Discussionmentioning
confidence: 99%
“…The medial longitudinal arch is the elastic and constrictive cambered structure in the foot, which has functions to support and maintain body balance during normal walking or with additional added weight (Zhao et al, 2018a;Zhao et al, 2018b). Foot morphology may change as a result of many factors, e.g., age, body weight, injury and type of footwear .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation